2020
DOI: 10.1097/qad.0000000000002474
|View full text |Cite
|
Sign up to set email alerts
|

Elite suppressors have low frequencies of intact HIV-1 proviral DNA

Abstract: Elite controllers or suppressors control viral replication without antiretroviral therapy. We used the intact proviral DNA assay to approximate the size of the inducible latent reservoir in elite suppressors and found that, while the median frequency of both total and intact proviral DNA was markedly lower than the frequencies seen in chronic progressors on antiretroviral therapy there was no significant difference in the ratio of intact to total proviral DNA between elite suppressors and chronic progressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…More recent studies of 61 and 50 participants reported failure rates of 9.8% and 12%, respectively 6 , 7 . The largest study undertaken to date using the IPDA, a multi-cohort study published by the assay’s developers, reports an overall failure rate of 6.3% of 400 participants 5 , although it is important to note that this study includes a number of published cohorts including four with 0% failure rates 4 , 8 – 10 . As such, the inferred failure rate for some of the unpublished datasets could be as high as 18%, a value that approaches the 28% rate reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies of 61 and 50 participants reported failure rates of 9.8% and 12%, respectively 6 , 7 . The largest study undertaken to date using the IPDA, a multi-cohort study published by the assay’s developers, reports an overall failure rate of 6.3% of 400 participants 5 , although it is important to note that this study includes a number of published cohorts including four with 0% failure rates 4 , 8 – 10 . As such, the inferred failure rate for some of the unpublished datasets could be as high as 18%, a value that approaches the 28% rate reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…While detection failures are expected for any molecular assay targeting a genetically variable pathogen, this rate has varied markedly across studies, ranging from 0% in the initial two reports (0/62 1 and 0/81 4 ) to 12% (6/50) in the most recent publication 7 , where the assay was performed by the same group. A recent multi-cohort study comprising 400 individuals reports an overall 6.3% failure rate 5 ; however, because this study includes the above 4 and other published cohorts with 0% failure rates 8 – 10 it can be inferred that the rates for the unpublished datasets are higher. Thus, while the IPDA is undeniably a major methodological advance, further study is needed to delineate the impact of HIV-1 sequence diversity.…”
Section: Introductionmentioning
confidence: 94%
“…The IPDA has already led to novel insights. For example, the assay has been used to provide more accurate estimates of the decay rate of the latent reservoir (19), to demonstrate differential decay rates for cells carrying intact and defective proviruses (9,19,20), to document low reservoir size in elite suppressors (21), and to explore the frequency and inducibility of intact HIV-1 proviruses in different subsets of CD4 + T cells (22).…”
mentioning
confidence: 99%
“…Recently Bruner et al developed a high throughput intact proviral DNA assay (IPDA) that approximates the frequency of intact proviruses as determined by full genome sequencing [25] . Kwaa et al used the IPDA to compare the size of the viral reservoir in patients on ART and ECs and found that the frequency of both total and intact DNA in EC was approximately 20-fold lower than the frequency seen in patients on ART [26] . Jiang and colleagues sequenced 1,385 and 2,388 full length proviral genomes from 64 ECs and 41 CPs respectively and also found significantly lower levels of intact and total DNA in ECs [27] .…”
Section: Evidence Of Replication-competent Virus In Ecsmentioning
confidence: 99%
“…Kwaa et al described a 200-fold variation in the level of intact proviral DNA that could be detected in the IPDA in ECs. One subject who has routinely had negative culture assays over greater than 10 years also had undetectable proviral DNA levels [26] . Jiang et al identified 2 EC who have extremely low levels of intact proviral DNA.…”
Section: Exceptional Elite Controllersmentioning
confidence: 99%